PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP PERKALIAN MELALUI PENDEKATAN PEMBELAJARAN KONSTRUKTIVISME PEMBELAJARAN MATEMATIKA DI KELAS 3 SDN CIBADUYUT 4 - Kusmawati, Linda; Ginanjar S, Gigin (STKIP Subang, 2016)
The learning approach that is held in generally still conventional still dominated by a class that focuses on teachers as the main source. Just as in mathematics, in learning the teacher directly convey the formulas, definitions, rules, laws, concepts, procedures, and algorithms. Learners are expected to mimic what the teacher described the math lessons that it provides. One of the many alternative approaches applied in teaching mathematics is to use a constructivist approach. This approach is an effort to improve understanding of the concept of learners towards learning mathematics. Constructivist learning approach assumes that learners should be active mentally build knowledge structures based on cognitive maturity has. With regard dengaan classroom action research that uses a constructivist approach in teaching mathematics to increase understanding of the concept of learning material multiplication in third grade at SDN Cibaduyut 4 Districts Bandung Kidul Bojongloa by the number of learners as many as 40 children. The instrument used in this study is a learning device that consists of a lesson plan and worksheets, data collection instruments consisted of the test and non-test. From the research we concluded that constructivist learning approach can improve understanding of the concept of multiplication for learners grade 3 SDN Cibaduyut 4. Seen from the attitude that learners can give a positive response to learning that have significant impact on the quality of the learning process and learning outcomes of students.